Impact of employment on women's empowerment in Uttar Pradesh: A geographical perspective - Shrinkhla Pandey; Gayatri Rai (National Geographical Journal of India, 2024)
Women's employment and education contribute significantly to empower as a result of their combined efforts and understanding of the supportive institutions that aids in this process. Gender equality and societal growth both depend upon the empowerment of women. Economic inequality and strongly ingrained cultural norms make women's empowerment in India, especially in the state of Uttar Pradesh, an enormous challenge. Based on secondary sources of data like the Census of India and NFHS-5, the study examines the socio-demographic covariables of women's employment and their influence on women's empowerment in the state of Uttar Pradesh. A clear profile of women's work participation can be obtained by using the cross-tabulation with background characteristics. Age, education, marital age, husband's desire for children, contraception, religion, and residential status are the predictors of the study. Social, economic, and cultural factors are primarily regarded as sub-dimensional explanatory variables. It concludes by pointing out the correlation between gender ratios and literacy in the state in 2011. The literacy rate in Uttar Pradesh has always been lower than all India's average. The correlation between Uttar Pradesh's sex ratio and literacy rate is fairly low and negative, with r = -0.56. The primary conclusion is that having a job positively affects, active the participation of women in household decision-making. Policymakers, NGOs, and campaigners working to improve the lives of women in the state can benefit greatly from the conclusions and suggestions made in this study.